Path-tracking Algorithm for Aircraft Fuel Tank Inspection Robots. (28th May 2014) - Guochen, Niu; Li, Wang; Qingji, Gao; Dandan, Hu
A 3D path-tracking algorithm based on end-point approximation is proposed to implement the path traversal of robots designed to inspect aircraft fuel tanks. Kinematic models of single-joint segments and multiple-joint segments were created. First, each joint segment of the path was divided into many equal sections and the rotation angle was computed. The rotation angle was found for the plane determined by one divided point and the secondary terminal joint segment. Second, the shortest distance search strategy was used to calculate the bending angle of the joint segment. The main advantage of the algorithm was that only the terminal joint segment variables needed to be solved, the joint variables of other joint segments were copied from the adjacent front-end joint segment variables in turn. Finally, evaluation indexes of path tracking performance were proposed to evaluate the effect of the algorithm. Simulations of planar and space path tracking were carried out using MATLAB, and the effectiveness and stability of the tracking algorithm were verified.